EFEKTIVITAS MODEL EDUKASI DAN DUKUNGAN MENYUSUI UNTUK MENINGKATKAN BREASTFEEDING SELF-EFFICACY DAN PEMBERIAN ASI EKSKLUSIF: SCOPING REVIEW - Sembiring, Gaipyana; Damayani, Ayi Diah; Aziz, Muhammad Alamsyah; Gurnida, Dida Akhmad (Media Penelitian dan Pengembangan Kesehatan, 2024)
WHO and UNICEF data state that the level of exclusive breastfeeding in the world is below the target of 40%. Breastfeeding self-efficacy was identified as one of the strongest modifiable predictors. This scoping review aimed to analyze the effectiveness of breastfeeding education models to increase breastfeeding self-efficacy and exclusive breastfeeding. The design of this article is a systematic review using the Preferred Reporting Items for Literature Review and Meta-Analyses (PRISMA) method. Article searches used electronic databases from Scopus, Science Direct, PubMed and Sage. The keywords in the article search are "Exclusive Breastfeeding", "Breastfeeding Education", and "Self-Efficacy". The inclusion criteria in this literature review were studies that have samples of pregnant women ≥ 30 weeks, normal pregnancies without complications. Criteria for babies to be born at term and have normal weight. The results of the scoping review show that the most effective breastfeeding education and support models are prenatal counselling, integrated breastfeeding education program and breastfeeding education with grandmothers' attention. The main characteristic is education carried out from antenatal to breastfeeding. Education is provided involving family members. Education is carried out in a multicomponent manner through breastfeeding training, home visits and post-natal telephone follow-up. The theoretical framework uses self-efficacy theory. The minimum educational frequency consists of 2-4 sessions with a minimum length of 40 minutes. It is hoped that the results of this review will serve as a guide for designing an effective exclusive breastfeeding education model by applying the five main characteristics to increase breastfeeding self-efficacy and exclusive breastfeeding.